Analysis of Healthcare Data of Nepal Hospital using Multinomial Logistic Regression Model - Yadav, Amit; Hui, Li; Ali, Mohsin; Anis, Maria (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Patient data had been collected from the hospital of Nepal with the help of hospital administration, doctors and patient cooperation. Data scrutiny attempts to shows the significant relationship between disease and factors causal of disease. Research explores the utility of multinomial logistic regression (MLR) technique in health domain and its most beneficial use for categorical data. Paper try to exhibit various factors which results in happening of health disorder and highlight application of data mining technique in healthcare. It is conceived that this work render more accuracy and reliability in detection of factors causal of disease, espial of fraud, helpful for all parties associated with healthcare, reduce cost, lessen time and treatment process.